Non-small cell lung cancer transdifferentiation into small cell lung cancer: A case series. (August 2018) - Ahmed, Tahreem; Vial, Macarena R.; Ost, David; Stewart, John; Hasan, Muhammad A.; Grosu, Horiana B.
Highlights: Transdifferentiation can occur in both adenocarcinoma and squamous cell carcinoma. Transdifferentiation can occur irrespective of EGFR mutation status or exposure to TKIs. Transdifferentiation occurred in 0.2% of lung cancer patients at our institution. Abstract: Transdifferentiation from non-small cell lung cancer (NSCLC) to small cell lung cancer (SCLC) has been reported mostly in adenocarcinomas and has been described as a cause of acquired tyrosine kinase inhibitor (TKI) resistance. However, transdifferentiation has also been described in patients with different histologic characteristics and patients not exposed to TKIs and with no epidermal growth factor receptor (EGFR) mutation (the target of TKIs). To this date transdifferentiation remains poorly understood. We conducted a retrospective case series of patients who had biopsy-proven SCLC within 2 years after a diagnosis of NSCLC or in the same location as the known primary NSCLC. We found that 0.2% of lung cancer patients at our institution experienced transdifferentiation. Among these, 30 had adenocarcinoma and 16 had squamous cell carcinoma. In 27 of the 30 patients with adenocarcinoma (90%), SCLC was found in the same location as the known primary. In 14 of the 30 patients (47%), SCLC occurred within 2 years after the NSCLC diagnosis. In 12 of the 16 patients with squamous cell carcinoma (75%), SCLC was found in the same location as the known primary. In 8 of these 16 patients (50%), SCLC occurred within 2 years after the NSCLC diagnosis. Few patients with adenocarcinoma and none with squamous cell carcinoma were treated with TKIs or had an EGFR mutation. In conclusion the findings in the current study suggest that the discovery of SCLC histology after treatment of NSCLC may be more common than thought suggesting that further study is warranted to evaluate the phenomenon of transdifferentiation.